2015
DOI: 10.5455/ijmsph.2015.2611201496
|View full text |Cite
|
Sign up to set email alerts
|

Awareness among junior residents regarding management of animal bite in a tertiary care hospital in Haryana

Abstract: occur in rural areas of Africa and Asia. In India alone, 20,000 deaths (i.e., about 2/100,000 population at risk) are estimated to occur annually. India has 36% global and 65% Asian rabies burden in terms of cases. [1-3] The majority of deaths (84%) occur in rural areas. The estimated annual cost of rabies is US$6 billion (95% CI, 4.6-7.3 billion), with almost US$2 billion (~40%) due to lost productivity after premature deaths and a further US$1.6 billion spent directly on postexposure prophylaxis. [4] There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…Our study found that over 50% of service providers were aware of the anti-RIG dose to be administered. This is similar to results obtained by Shashikantha, who showed that 52% of service providers were aware of the anti-RIG dose [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that over 50% of service providers were aware of the anti-RIG dose to be administered. This is similar to results obtained by Shashikantha, who showed that 52% of service providers were aware of the anti-RIG dose [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…This is a problem as the category of wound determines the appropriate treatment [ 17 ]. In contrast, a study conducted in North India found that 50% of service providers had knowledge about the correct categorization of animal bite wounds [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,9,12 Also, the majority (84%) could correctly classify category III bite which was lower than the findings of Giri et al (88.1%) but higher than the findings of Sarkar et al (57%) and Shashikantha et al (72%). 4,9,12 Only 26.5% knew the correct management of Cat I animal bite which was higher than the findings of Chowdhury et al (10%). 6 The majority (74.5%) knew the correct management of Cat II animal bite which was higher than the findings of Chowdhury et al (57.5%) and 89% knew the correct management of Cat III animal bite which was near the findings of Chowdhury et al (85%).…”
Section: Discussioncontrasting
confidence: 58%
“…8,11 The majority (87%) could correctly classify category I bite which was higher than the findings of Giri et al (77.6%), Sarkar et al (67%), and Shashikantha et al (62%). 4,9,12 Similarly, the majority (86%) could correctly classify category II bite which was higher than the findings of and Giri et al (81.6%), Sarkar et al (19%) and Shashikantha et al (66%). 4,9,12 Also, the majority (84%) could correctly classify category III bite which was lower than the findings of Giri et al (88.1%) but higher than the findings of Sarkar et al (57%) and Shashikantha et al (72%).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation